Analisis Efesiensi Dan Efektifitas Layout Fasilitas Proses Produksi : (Studi Kasus Pada PT. Herlina Pratama Putra) - Risdayanti Risdayanti (CV. ULIL ALBAB CORP, 2022)
This study aims to determine the layout of the production process facilities applied by PT. Herlina Pratama Putra, knowing the layout of the production process facilities using the line balancing method at PT. Herlina Pratama Putra and knows the application of a more efficient and effective layout without the line balancing method or using the line balancing method. The technical analysis of the data used in this study is the calculation using the line balance method. The results of this study indicate that the type of layout applied by the company is product layout. The layout of the production process facilities using the line balancing method in the company must use 4 work stations, but in reality there are only 2 work stations. The application of a more efficient and effective layout for the company is using the line balancing method, because at the time of the work cycle in real conditions of 20 minutes without using the line balancing method, it can be seen that the total idle time is 5 minutes with an efficiency level of 87.5%, effectiveness of 40% and the percentage of idle time is 12.5%. While the work cycle time based on the work cycle time based on real conditions, namely 20 minutes using the line balancing method, it can be seen that the total idle time is 5 minutes with an efficiency level of 93.75%, effectiveness 40% and the percentage of idle time is 6 ,25%.